Explaining Enterprise Performance in Developing Countries with Business Climate Survey Data - Dethier, Jean-Jacques (Washington, DC: World Bank, 2012)
This paper surveys the recent literature which examines the impact of business climate variables on productivity and growth in developing countries using enterprise surveys. Comparable enterprise surveys today cover some 70,000 firms in over 100 countries around the world. The literature that has analyzed this data provides evidence that a good business climate drives growth by encouraging investment and higher productivity. Various infrastructure, finance, security, competition and regulation variables have been shown to significantly impact firm performance. Section 1 of this paper outlines the theoretical framework that underpins the investment climate literature. Section 2 describes the available datasets and surveys the key findings of the empirical literature, first macroeconomic and then microeconomic studies. Particular attention is paid to the robustness of the reported results. Section 3 highlights important econometric issues common to this literature and suggests a research agenda and possible improvements in survey design.